2012
DOI: 10.1111/j.1477-2574.2012.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Centre volume and resource consumption in liver transplantation

Abstract: This UHC-based cohort shows that increased centre volume results in improved long-term post-liver transplant outcomes and more efficient use of hospital resources thereby lowering the cost. A better understanding of these mechanisms can lead to informed decisions and optimization of the pay for performance model in liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 29 publications
1
54
1
1
Order By: Relevance
“…Eight studies could not be included in the fi nal analyses because they had insuffi cient data to calculate OR. 19,21,41,44,51,53,54,56 Th e results of these studies are presented in Table 2 . Among the remaining studies (n 5 37), the consistency of the relationship varied considerably across diagnoses.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies could not be included in the fi nal analyses because they had insuffi cient data to calculate OR. 19,21,41,44,51,53,54,56 Th e results of these studies are presented in Table 2 . Among the remaining studies (n 5 37), the consistency of the relationship varied considerably across diagnoses.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…16,18,19 Seven clinical conditions were covered: respiratory diagnoses including mechanical ventilation, acute respiratory failure, and pneumonia (13 studies) 15,16,[20][21][22][23][24][25][26][27][28][29][30] ; cardiovascular diagnoses including cardiac arrest and cardiogenic shock (eight studies) [31][32][33][34][35][36][37][38] ; sepsis (six studies) [39][40][41][42][43][44] ; neurologic diagnoses (three studies) 15,45,46 ; hepato-GI diagnoses (three studies) 15,47,48 ; renal diagnoses (three studies) 17,49 ; and postoperative conditions including pancreatectomy, hepatectomy, esophagectomy, major vascular surgery (seven studies). [50][51][52][53][54][55][56] The majority of studies (n 5 24, 52%) used clinical databases rather than administrative databases. Th e most common unit of analysis used was hospital volume (n 5 25, 54%), followed...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous kidney and liver transplant studies demonstrate significant variation in transplant admission cost and EHR among centers, with transplant center volume contributing to variation (4)(5)(6)(7)(8)(9)(10)(11)(12). For instance, concerning liver transplants, highvolume centers have lower transplant admission cost than intermediate-and low-volume centers (5).…”
mentioning
confidence: 99%
“…192 Another earlier study found that outcomes were better in patients transplanted in centers performing more than 20 transplants/year versus less than 20 transplants/year, whereas, a study by Nijboer et al 193,194 did not find a clear correlation between center activity and outcomes in 24 liver transplant units in Germany. In a similar US-based study, Macomber et al 195 found lower mortality rates in higher-volume centers, with lower median length of hospital and intensive care unit stay and lower direct costs. Others have failed to demonstrate an effect of volume.…”
Section: Provision Of Transplant Unitsmentioning
confidence: 90%